Relationship between objectively measured conversation time and social behavior in community-dwelling older adults - Kimura, Noriyuki; Masuda, Teruaki; Ataka, Takuya; Matsubara, Etsuro (Frontiers in Neurology, 2024)
Background Social isolation is a significant public health concern in aging societies. The association between conversation time and social behavior remains unclear. This study examines whether objective conversation time is associated with social activity frequency in older adults. Methods This prospective cohort study enrolled 855 older adults (538 women; mean age, 73.8 years) aged 65 and older, who were followed from 2015 to 2019. All participants wore a wristband sensor to measure conversation time for at least 9 days and an average of 31.3 days per year. Social behaviors were assessed through interviews, and the frequency of engagement in community activities, outings, lessons, or classes and contact frequency were assessed using a self-report questionnaire. The association between conversation time and social behavior was evaluated using multi-linear regression analysis. Results Conversation time was significantly associated with the frequency of engagement in community activities and lessons or classes after adjusting for several covariates (β = 0.181, 95% confidence interval: 0.107–0.254, p < 0.001; β = 0.11, 95% confidence interval: 0.04–0.179, p = 0.002). Conclusion Objectively measured conversation time using a wearable sensor is associated with social behavior and may be a valuable parameter for social isolation in older adults.